Taxing Multinationals in the Presence of Internal Capital Markets - Marko Koethenbuerger; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2013)
There is ample evidence that internal capital markets incur efficiency costs for multinational enterprises (MNEs). This paper analyzes whether tax avoidance behavior interacts with the costs of running an internal capital market and how policies of competing governments respond to it. We show that the interaction in itself may lead to profit taxes that are too high (low) from a social perspective, provided the costs are attenuated (magnified) by higher profit taxes. We also show that internal efficiency costs might render infrastructure provision inefficiently low. Further, we clarify the implications of the MNE's decision to set up an internal capital market and the effect of external finance on the behavior of competing governments.
Keywords: H25; D21; F23; 330; fiscal competition; multinational firms; internal efficiency costs; corporate finance; corporate tax avoidance